Perceived helpfulness of the individual components of a behavioural weight loss program: results from the Hopkins POWER Trial. (9th September 2015) - Dalcin, A. T.; Jerome, G. J.; Fitzpatrick, S. L.; Louis, T. A.; Wang, N‐Y.; Bennett, W. L.; Durkin, N.; Clark, J. M.; Daumit, G. L.; Appel, L. J.; Coughlin, J. W.
Summary Background Behavioural weight loss programs are effective first‐line treatments for obesity and are recommended by the US Preventive Services Task Force. Gaining an understanding of intervention components that are found helpful by different demographic groups can improve tailoring of weight loss programs. This paper examined the perceived helpfulness of different weight loss program components. Methods Participants (n = 236) from the active intervention conditions of the Practice‐based Opportunities for Weight Reduction (POWER) Hopkins Trial rated the helpfulness of 15 different components of a multicomponent behavioural weight loss program at 24‐month follow‐up. These ratings were examined in relation to demographic variables, treatment arm and weight loss success. Results The components most frequently identified as helpful were individual telephone sessions (88%), tracking weight online (81%) and coach review of tracking (81%). The component least frequently rated as helpful was the primary care providers' general involvement (50%). Groups such as older adults, Blacks and those with lower education levels more frequently reported intervention components as helpful compared with their counterparts. Discussion Weight loss coaching delivered telephonically with web support was well received. Findings support the use of remote behavioural interventions for a wide variety of individuals.